Prevalence and Risk Factors of Gastroesophageal Reflux Disease Among the Study Population: A Cross-Sectional Study - Sheikh Muhammad Taqqi Anwar, Mohsin Ali, Khadim Hussain Samejo, Hyder Wajid Abbasi, Nazeer Ahmed, Nadeem (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the prevelance and risk factors of gastroesophageal reflux disease among the study population Study design: A cross-sectional study Place and Duration: This study was conducted at Poonch Medical College Rawalakot AJK Pakistan from January 2020 to January 2021. Methodology: This study was conducted on a sample size of 302 people utilizing a researcher-created checklist and questionnaire. The survey was made available on the internet. The data was analyzed using SPSS version 22, which comprised the Chi-square test and descriptive statistics. Questions about increased pain intensity, food intake or not, and other signs and symptoms of reflux and factors that could increase chances of risk such as drinking coffee, smoking, spicy food, certain types of drugs, and alcohol were determined. We also inquired as to whether any investigations had been conducted. Results: The cumulative prevalence of GERD among the individuals was 61.7 percent. Significant discomfort was seen in 12 percent of the cases. Furthermore, 61.7% reported lack of appetite, 55.8% indigestion, 57% nausea and vomiting, 55.5% food regurgitation, and 41.5% chest discomfort as an associated symptom. The primary risk factors discovered were coffee consumption in 77.5%, spicy food in 58.0%, smoking in 17.1% fatty meals in 84.8%, NSAD in 24.5%, and stress in 71% participants. There was no significant difference in the occurrence of GERD based on educational level, age, employment status, marital status, or gender. Conclusion: The percentage of gastroesophageal reflux disease (61.7 percent) was extremely high. Spicy foods, coffee use, fatty meals, smoking and stress were identified as factors that increased risk. Endoscopic investigations on a population basis are advised.